Towards Equitable Diabetes Care: A Global Perspective on Quality Measurement Exchange - Alon Rasooly; Orly Manor; Ruitai Shao; Moriah E. Ellen; Nadav Davidovitch (Health Systems & Reform)
In the pursuit of equitable diabetes care, international knowledge exchange (iKE) serves as a crucial mechanism for narrowing the gaps in quality within and between countries. Little is known about the process of quality measurement exchange among stakeholders from high-income countries (HICs), low- and middle-income countries (LMICs), and international organizations. This study aims to analyze recent international exchanges of quality measures in diabetes care and propose a framework for enhancing quality, focusing on LMICs. Employing a realist evaluation methodology, we conducted database searches for peer-reviewed articles, international organizations’ documents, and country-level reports. Semi-structured online interviews were conducted with corresponding authors. Synthesis was achieved using the Two-Communities theory. The study encompassed 98 articles and reports from 44 countries and regions, supplemented by in-depth interviews with 13 informants. We delineate a framework for iKE of quality measures, highlighting three key approaches: “pull,” “push,” and “exchange.” Researchers in HICs and LMICs utilize knowledge from other countries, adapting to local contexts through various processes. International organizations such as the World Health Organization and the International Diabetes Federation play pivotal roles in developing and disseminating measurement tools. “Exchange” processes expedite sharing, especially in LMICs, empowering local stakeholders. Global inequities in quality measurement underscore the need for collaborative efforts to address the Inverse Care Law. Finally, a realist framework was developed to guide stakeholders in identifying relevant iKE initiatives, facilitating gradual improvements in quality measurement. Balancing measurement burden with clinical care while strengthening primary care capacity and data systems is crucial for advancing equitable diabetes care globally.